2021
DOI: 10.1021/acsomega.1c00440
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fluorescent Probe toward Fe3+ Based on Rhodamine 6G Derivatives and Its Bioimaging in Adult Mice, Caenorhabditis elegans, and Plant Tissues

Abstract: A new fluorescent probe LXY based on the rhodamine 6G platforms has been designed, synthesized, and characterized, which could recognize Fe3+ effectively in HEPES buffer (10 mM, pH = 7.4)/CH3CN (2:3, v/v). And the distinct color change and the rapid emergence of fluorescence emission at 550 nm achieved “naked eye” detection of Fe3+. The interaction mode between them was achieved by Job’s plot, MS, SEM, and X-ray single-crystal diffraction. Importantly, the crystal structures proved that Fe3+ could induce the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Studies with L-02 cells and PC-12 rat pheochromocytoma cells confirmed its application in detecting exogenous Fe­(III) in subcellular regions. Dyes 78 , 79 , 80a , and 81 – 83 similarly contain an amide linkage between the rhodamine and recognition unit, and respond to Fe­(III) through a spirolactam ring-opening. In addition, dyes 80b , 84 , and 85 are examples in which two rhodamine units were joined together in such a manner that the probe can coordinate two ferric ions simultaneously, resulting into a strong turn-on response (560-585 nm) owing to the ring opening of rhodamine. ,, These probes were then employed for cellular imaging of Fe­(III) ions in PC-12, human gastric cell line (SGC-7901) and MCF-7 cells respectively. Dyes RBCS ( 86 ) and RBTM ( 87 ) are two thioamide-containing rhodamine B-based probes that selectively bind to Fe­(III) in the ring-opened form to produce a strong fluorescence emission. , These probes were employed in HeLa and MKN-45 human gastric cancer cells, respectively, to visualize exogenously added ferric ions.…”
Section: Fluorescent Sensors For Ironmentioning
confidence: 99%
“…Studies with L-02 cells and PC-12 rat pheochromocytoma cells confirmed its application in detecting exogenous Fe­(III) in subcellular regions. Dyes 78 , 79 , 80a , and 81 – 83 similarly contain an amide linkage between the rhodamine and recognition unit, and respond to Fe­(III) through a spirolactam ring-opening. In addition, dyes 80b , 84 , and 85 are examples in which two rhodamine units were joined together in such a manner that the probe can coordinate two ferric ions simultaneously, resulting into a strong turn-on response (560-585 nm) owing to the ring opening of rhodamine. ,, These probes were then employed for cellular imaging of Fe­(III) ions in PC-12, human gastric cell line (SGC-7901) and MCF-7 cells respectively. Dyes RBCS ( 86 ) and RBTM ( 87 ) are two thioamide-containing rhodamine B-based probes that selectively bind to Fe­(III) in the ring-opened form to produce a strong fluorescence emission. , These probes were employed in HeLa and MKN-45 human gastric cancer cells, respectively, to visualize exogenously added ferric ions.…”
Section: Fluorescent Sensors For Ironmentioning
confidence: 99%
“…Guo 2014; Ozdemir, Zhang, and Guo 2018;Aydin et al 2020). Another mechanism without the involvement of direct Fe 3þ -coordination, instead, a Fe 3þ -induced ring-opening of the rhodamine spiroclic lactone was proposed recently in a new rhodamine-based Fe 3þ probe RXY (Zhang et al 2021). However, RXY has a much lower Fe 3þ -binding constant (3.0 Â 10 4 M À1 ) (Zhang et al 2021) than for RhPK (1.54 Â 10 7 M À1 ).…”
Section: Reversibility In Fe 31 -Bindingmentioning
confidence: 99%
“…Interestingly, a number of "turn-on" or ratio metric probes for Fe 3þ have recently been reported (Aydin, Wei, and Guo 2012;Wei et al 2012;Zhu et al 2016;Zhou et al 2017;Qiao et al 2018;Wu et al 2019;Shellaiah et al 2020;Ghosh et al 2020;Li et al 2016;Liu et al 2020;Yang et al 2020;Kaur, Kaur, and Kumar 2018;Zhang et al 2014;Lohani and Lee 2010;Heng et al 2008;Ackerman, Lee, and Chang 2017;Lee et al 2016;Wang et al 2010;Mir et al 2019;Qiu et al 2014;Vishaka et al 2019;Kim et al 2019;Jothi et al 2021;Gao et al 2020;Zhang et al 2021;Wei et al 2010). Many iron probes, especially turn-on and ratiometric Fe 3þ probes, have been discussed in detail in recent review papers Crisponi 2019, Sun, Sun, andGuo 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation